Elevers berättelser om sina upplevelser av högstadiet - Andersson, Helena (Educare, 2014)
The voices of students are not often heard in a research context. This article focuses ten students’ experiences of the educational settings they were a part of, especially the settings in secondary school. Through stories from the ten students the article attempts to illuminate conditions for making an educational setting inclusive. The stories show that schools’ organizations and the relations with the teachers might be such conditions. Another condition for students seems to be to actively take part and to be engaged in their education. These conditions are important for the students’ possibilities to achieve their educational goals. The conditions are also important in order to avoid marginalization of the students.